1991
DOI: 10.1172/jci115062
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol ameliorates the development of portal-systemic shunting in a chronic murine schistosomiasis model of portal hypertension.

Abstract: We investigated the role of early portal hypotensive pharmacotherapy in preventing the development of portal-systemic shunting in a portal hypertensive model of chronic murine schistosomiasis induced by infecting C3H mice with 60 cercariae of Schistosoma mansoni. Propranolol was administered in drinking water to 20 animals for a period of6 wk at a dose of 10 mg -kg-'d-1, starting at 5 wk of schistosomal infection. 32 agematched mice with chronic schistosomal infection served as controls. All animals were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
11

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 23 publications
3
33
0
11
Order By: Relevance
“…Experimental models of portal hypertension have shown that B-Blockers delay the development of collaterals [24,25] . Escorsell et al [26] demonstrated that administration of β-blockers (timolol) to patients without varices caused a greater reduction in portal pressure than the reduction seen in patients with varices [26] .…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…Experimental models of portal hypertension have shown that B-Blockers delay the development of collaterals [24,25] . Escorsell et al [26] demonstrated that administration of β-blockers (timolol) to patients without varices caused a greater reduction in portal pressure than the reduction seen in patients with varices [26] .…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…El riesgo de hemorragia variceal disminuye cuando se reduce el GPVH, indicando que la reducción de la presión portal es la diana más efectiva para impedir la formación y/o el desarrollo de vasos colaterales. Sin embargo, aunque en modelos experimentales de cirrosis se ha podido prevenir la formación de colaterales al administrar fármacos que disminuyen la presión portal, como el propanolol (35), ello no ha sido así en enfermos con cirrosis compensada tratados con betabloqueantes no selectivos (36). La hiperemia esplácnica y el aumento del aflujo venoso portal es la segunda fuerza promotora del desarrollo de colaterales.…”
Section: Fisiopatología De La Hipertensión Portal En La Cirrosisunclassified
“…En estos modelos experimentales se comprobó que era posible reducir la formación de colaterales portosistémicas causando vasoconstricción arteriolar y atenuación de la hiperemia esplácnica, como factores responsables de la colateralización portosistémica. Ello puede lograrse administrando bloqueantes beta-adrenérgicos no selectivos (35,49,50), como el propanolol, o inhibidores de la síntesis de ON, como los análogos de la L-arginina (24), o anticuerpos monoclonales frente al TNF-alfa (29). Sarin y cols.…”
Section: Modulación De La Formación De Colaterales Portosistémicas Enunclassified
See 2 more Smart Citations